Distribution of the Termite Reproductive Castes in Gunungpati, Semarang, Central Java - Niken Subekti; Saniaturrohmah Saniaturrohmah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Soil termites play a role as a primary decomposer in natural forests. These types of termites can be turned into residential pests as more land use to be plantations, housing, and buildings. This study analyzed the distribution of subterranean termites' reproductive caste, its identification, and environmental factors that influence the development of subterranean termites. The research methods used include distribution analysis using UV flying traps, surveys using GPS, identification of reproductive castes, and environmental factors including soil nutrients, vegetation analysis, temperature, soil moisture, air humidity, and wind speed. The results showed that the distribution of termites is found throughout the Gunungpati Semarang area. The identification of reproductive caste/alates found was Termitidae. Environmental factors that affect the life of termites in the Gunungpati Semarang area December 2019-January 2020 include the temperature of 27.0-28.4 oC, the humidity of 60.2 -61.2 %, air pressure 950.5-975.0 hPa, soil pH 4.84 - 5.60 and soil moisture 29.7-34.0 %. The vegetation was dominated by the Apocynaceae, Sapindaceae, and Euphorbiaceae. The highest value of diversity and vegetation index sequentially are Sekaran, Patemon, and Ngijo. It is found that the entire Gunungpati area of Semarang is a suitable habitat for the growth and development of the Termitidae. The finding will help the authoritative institution to consider Gunungpati as a conservation area.